A high-performance visible-light-driven all-optical switch enabled by ultra-thin gallium sulfide. Issue 9 (5th February 2021) - Xu, Kai; Zhang, Bao Yue; Hu, Yihong; Khan, Muhammad Waqas; Ou, Rui; Ma, Qijie; Shangguan, Chunmei; Murdoch, Billy J.; Chen, Weijian; Wen, Xiaoming; Ren, Guanghui; Ou, Jian Zhen
Abstract : A 2D Ga2 S3 enabled all-optical switch is realized upon a silicon-based on-chip platform. With the unique optical properties of the 2D nanoflakes, the device exhibits excellent switching behaviors driven by visible light at a low power density. Abstract : On-chip optical switches have emerged as a new class of photonic components for high-performance optical communication networks and on-chip interconnects, in which the all-optical configuration without the incorporation of other control-means is highly desired. While two-dimensional (2D) ultrathin materials demonstrate their great potential in developing ultrafast all-optical switches owing to their unique light–matter interaction, such investigations have so far been limited to the fiber optic platform or free space. Here, we realize an all-optical on-chip switch from a silicon waveguide-based asymmetric Mach–Zehnder interferometer (MZI) structure enabled by 2D ultrathin Ga2 S3 . Upon the visible light excitation at 532 nm, excessive photocarriers in Ga2 S3 cause a change of the refractive index and subsequently a phase variation between MZI arms at the 1550 nm operation wavelength, triggering on the optical switch. On the other hand, the switch is off without the visible light stimulation, as the phase variation is recovered due to the ultrafast photo-exciton relaxation behavior of Ga2 S3 . The Ga2 S3 -enabled all-optical switch is driven at an extremely small optical power density of 0.12 W cm −2 and exhibits a response and recovery time of 26.3 and 43.5 μs, respectively, which as a combination is superior to those of fiber optic-based all-optical switches enabled by 2D materials. This work may provide a viable approach to develop on-chip all-optical photonic components for practical integrated photonic chips.